Oliver - Sif, Birgitta 1981- (Walker, 2012)
Oliver is different. He enjoys his solitude. With his rich imagination, Oliver's day is never dull. There are bridges to cross, sharks to fight, and treasures to find! But maybe toys do not always give a boy everything he needs. Maybe he needs another kind of companion. Will Oliver discover a way to be, well, different?